A Photosynthesis-Specific Rubredoxin-Like Protein Is Required for Efficient Association of the D1 and D2 Proteins during the Initial Steps of Photosystem II Assembly. Issue 9 (18th July 2019) - Kiss, Éva; Knoppová, Jana; Aznar, Guillem Pascual; Pilný, Jan; Yu, Jianfeng; Halada, Petr; Nixon, Peter J.; Sobotka, Roman; Komenda, Josef
Abstract : The rubredoxin-like protein conserved in oxygenic phototrophs binds to the D1 protein and facilitates the formation of the D1/D2 heterodimeric reaction center complex of PSII. Abstract: Oxygenic photosynthesis relies on accessory factors to promote the assembly and maintenance of the photosynthetic apparatus in the thylakoid membranes. The highly conserved membrane-bound rubredoxin-like protein RubA has previously been implicated in the accumulation of both PSI and PSII, but its mode of action remains unclear. Here, we show that RubA in the cyanobacterium Synechocystis sp PCC 6803 is required for photoautotrophic growth in fluctuating light and acts early in PSII biogenesis by promoting the formation of the heterodimeric D1/D2 reaction center complex, the site of primary photochemistry. We find that RubA, like the accessory factor Ycf48, is a component of the initial D1 assembly module as well as larger PSII assembly intermediates and that the redox-responsive rubredoxin-like domain is located on the cytoplasmic surface of PSII complexes. Fusion of RubA to Ycf48 still permits normal PSII assembly, suggesting a spatiotemporal proximity of both proteins during their action. RubA is also important for the accumulation of PSI, but this is an indirect effect stemming from the downregulation of light-dependent chlorophyll biosynthesis induced by PSII deficiency. Overall, our data support the involvement of RubA in the redox control of PSII biogenesis.